Sidedness matters: single-cell perspectives on left- and right-sided colorectal cancer - Yanova, Maria; Maltseva, Diana; Tonevitsky, Alexander (Frontiers in Cell and Developmental Biology, 2025)
Colorectal cancer (CRC) remains one of the leading causes of cancer-related morbidity and mortality worldwide. Tumor sidedness, distinguishing left- (LCRC) and right-sided (RCRC) cancers, has emerged as a critical clinical determinant, influencing patient prognosis and therapeutic response. However, the cellular and molecular mechanisms underlying these differences remain poorly understood. Recent advances in single-cell RNA sequencing (sc-seq) provide high-resolution insights into CRC heterogeneity, revealing distinct tumor, immune, and stromal cell populations and their context-specific interactions. In this review, we synthesize sc-seq studies that dissect the molecular programs driving progression, therapy resistance, and metastasis in CRC. We highlight malignant subclusters characterized by metabolic reprogramming and spatially organized oncogenic signaling; specialized immune cell states, including macrophage subsets, exhausted T cells, and mast cells, that shape tumor immunity; and stromal elements such as cancer-associated fibroblasts and endothelial tip cells that remodel the extracellular matrix, promote angiogenesis, and foster immune evasion. Importantly, sc-seq demonstrates that LCRC and RCRC represent distinct multicellular ecosystems with differential immune recruitment and stromal signaling, underscoring the need for sidedness-informed therapeutic strategies. We propose that future interventions should target cell-cell communication networks and spatially defined tumor–microenvironment interactions to overcome heterogeneity and improve clinical outcomes.